Does pediatric heart transplant survival differ with various cardiac preservation solutions?. Issue 12 (22nd November 2020) - Shaw, Taylor B.; Lirette, Seth; Carter, Kristen T.; Kutcher, Matthew E.; Baran, David A.; Copeland, Jack G.; Copeland, Hannah
Abstract: Background: Few studies directly compare outcomes between the most commonly used preservation solutions in pediatric heart transplantation in a large cohort of recipients. The purpose of this study is to investigate the effect of cardiac preservation solution on survival in pediatric heart transplant recipients. Methods: The United Network for Organ Sharing (UNOS) database was retrospectively reviewed from 01/2004‐03/2018 for pediatric donor hearts. Saline, University of Wisconsin (UW), "cardioplegia, " Celsior, and Custodiol preservation solutions were evaluated. The primary endpoints were recipient survival at 30 days, 1 year, and long term. Results: After exclusion criteria, 3012 recipients had preservation solution data available. The most common preservation solution used was UW in 1203 patients (40%), followed by Celsior in 542 (18%), cardioplegia in 461 (15%), saline in 408 (14%), and Custodiol in 398 (13%). Survival of recipients whose donor hearts were procured with UW was as follows: 97%—30 day, 92%—1 year; Celsior: 97%—30 day, 92%—1 year; cardioplegia: 97%—30 day, 91%—1 year; saline: 97%—30 day, 91%—1 year; and Custodiol: 96%—30 day and 92%—1 year. Analysis of Cox models for 30‐day and long‐term survival revealed no statistical differences when comparing UW to Celsior ( p  = .333), cardioplegia ( p  = .914), saline ( p  = .980), or Custodiol ( p  = .642) in adjusted models. Conclusions: There were no significant differences in 30‐day or 1‐year survival detected between commonly used preservation solutions in the pediatric heart transplant population.